Design and preparation of organic small molecules in NIR-II and their application in fluorescence imaging/photothermal therapy/ photoacoustic imaging. (February 2023) - Wang, Yu; Liu, Xinyu; Liu, Chang; Su, Yingbin; Cong, Hailin; Gong, Shida; Yu, Bing; Shen, Youqing
Abstract: Recently, organic small molecule probes with good development potential have attracted extensive attention from researchers due to their advantages such as controllable structure, good biocompatibility, fast excretion rate and no long-term toxicity. Among various types of organic small molecule probes, it is worth mentioning that the emergence of fluorescent probes with donor-acceptor-donor (D-A-D) structure plays an important role. Thanks to this, recently, many studies have focused on further modification of the molecular skeleton of D-A-D structure in order to further improve the fluorescence performance. In view of the fact that the synthesis of organic fluorescent small molecules with S-D-A-D-S structure by introducing a shielding unit proved to be effective in obtaining fluorescent molecules with increased quantum yield, an organic fluorescent molecule with D-A-D structure is designed in this paper, and an organic fluorescent molecule with S-D-A-D-S structure is synthesized on the basis of the original structure by introducing a shielding unit, which is used in fluorescence imaging, photothermal therapy and photoacoustic imaging. Graphical abstract: Image 1 Highlights: D-A-D type and S-D-A-D-S type organic small molecule fluorescent probes with NIR-II properties were prepared. S-D-A-D-S type organic small molecule fluorescent probe has better quantum yield. Their applications in photothermal treatment, fluorescence and photoacoustic imaging were explored.